A Novel Silicon-Based Electrochemical Treatment to Improve Osteointegration of Titanium Implants. Issue 2 (May 2013) - Valle, Cinzia Della; Rondelli, Gianni; Cigada, Alberto; Bianchi, Andrea Edoardo; Chiesa, Roberto
Background: Titanium and its alloy represent the most commonly used biomaterials worldwide designed for bone-contact under-load applications, which often require specific mechanical properties. In particular, a large number of different biomimetic surface treatments have been developed to speed up the osteointegration process, which facilitates a reduction in recovery time. Purpose: The aim of this work is to investigate the physical-chemical, mechanical and bioactivity properties of an innovative biomimetic treatment on titanium performed using Anodic Spark Deposition (ASD) electrochemical treatment. Methods: The proposed Asd treatment was obtained in an electrochemical solution containing silicon, calcium, phosphorous and sodium followed by an alkali etching. Surface morphology was characterized using SEM and laser profilometry. Chemical and structural composition was assessed by EDS, ICP/OES and XRD analysis. Vickers micro hardness and static contact angle measurements were performed to assess the surface mechanical properties and wettability. Results: The proposed anodization treatment was capable of providing a chemical and morphologic modified titanium oxide layer, adherent and characterized by superhydrophilic properties. The microporous morphology was enriched by calcium, silicon, sodium and phosphorous. After incubation in Kokubo's simulated Body Fluid (sBF) the treatment showed very high mineralization potential compared to the reference surfaces, accounting for a deposited hydroxyapatite layer as thick as 12 μm after 14 days of SBF incubation. Conclusions: on the basis of the results obtained in this study, we believe that the novel silicon-based ASD biomimetic treatment represents a promising treatment capable of enhancing the osteointegration of titanium for dental and orthopedic applications.